Prognostic implications of systemic immune-inflammation index in patients with bone metastases from hepatocellular carcinoma treated with radiotherapy - Chen, Jingyao; Huang, Wenhan; Xu, Xiaohong; Fan, Shaonan; Zhang, Qi; Li, Xuan; Zeng, Zhaochong; He, Jian (Frontiers in Oncology, 2023)
Background: Previous studies have shown that systemic inflammation indicators could predict the survival outcomes of patients with malignant tumors receiving various treatments. Radiotherapy, as a crucial treatment modality, effectively alleviates discomfort in patients with bone metastasis (BM) and greatly improves the quality of life for them. This study aimed to investigate the prognostic value of systemic inflammation index in hepatocellular carcinoma (HCC) patients with BM treated with radiotherapy. Methods: We retrospectively analyzed clinical data collected from HCC patients with BM who received radiotherapy in our institution between January 2017 and December 2021. The pre-treatment neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and systemic immune-inflammation index (SII) were derived to determine their relationship with overall survival (OS) and progression-free survival (PFS), using the Kaplan-Meier survival curves. The optimal cut-off value of the systemic inflammation indicators for predicting prognosis was assessed by receiver operating characteristic (ROC) curves. Univariate and multivariate analyses were performed to ultimately evaluate the factors associated with survival. Results: The study included 239 patients with a median 14-month follow-up. The median OS was 18 months (95% confidence interval [CI] = 12.0-24.0) and the median PFS was 8.5 months (95% CI = 6.5-9.5). The optimal cut-off values for the patients were determined by ROC curve analysis as follows: SII =395.05, NLR=5.43 and PLR = 108.23. The area under the receiver operating characteristic curve values for SII, NLR and PLR in disease control prediction were 0.750, 0.665 and 0.676, respectively. Elevated systemic immune-inflammation index (SII>395.05) and higher NLR (NLR>5.43) were independently associated with poor OS and PFS. In multivariate analysis, Child-Pugh class (P = 0.038), intrahepatic tumor controlled (P = 0.019), SII (P = 0.001) and NLR (P = 0.007) were independent prognostic factors of OS and Child-Pugh class (P = 0.042), SII (P < 0.001) and NLR (P = 0.002) were independently correlated with PFS. Conclusion: NLR and SII were associated with poor prognosis in HCC patients with BM receiving radiotherapy and might be considered reliable and independent prognostic biomarkers for HCC patients with BM.